H3S10ph broadly marks early-replicating domains in interphase ESCs and shows reciprocal antagonism with H3K9me2 - Chen, Carol C.L.; Goyal, Preeti; Karimi, Mohammad M.; Abildgaard, Marie H.; Kimura, Hiroshi; Lorincz, Matthew C. (Genome Research, 2018)
Phosphorylation of histone H3 at serine 10 (H3S10ph) by Aurora kinases plays an important role in mitosis; however, H3S10ph also marks regulatory regions of inducible genes in interphase mammalian cells, implicating mitosis-independent functions. Using the fluorescent ubiquitin-mediated cell cycle indicator (FUCCI), we found that 30% of the genome in interphase mouse embryonic stem cells (ESCs) is marked with H3S10ph. H3S10ph broadly demarcates gene-rich regions in G1 and is positively correlated with domains of early DNA replication timing (RT) but negatively correlated with H3K9me2 and lamin-associated domains (LADs). Consistent with mitosis-independent kinase activity, this pattern was preserved in ESCs treated with Hesperadin, a potent inhibitor of Aurora B/C kinases. Disruption of H3S10ph by expression of nonphosphorylatable H3.3S10A results in ectopic spreading of H3K9me2 into adjacent euchromatic regions, mimicking the phenotype observed in Drosophila JIL-1 kinase mutants. Conversely, interphase H3S10ph domains expand in Ehmt1 (also known as Glp) null ESCs, revealing that H3S10ph deposition is restricted by H3K9me2. Strikingly, spreading of H3S10ph at RT transition regions (TTRs) is accompanied by aberrant transcription initiation of genes co-oriented with the replication fork in Ehmt1−/− and Ehmt2−/− ESCs, indicating that establishment of repressive chromatin on the leading strand following DNA synthesis may depend upon these lysine methyltransferases. H3S10ph is also anti-correlated with H3K9me2 in interphase murine embryonic fibroblasts (MEFs) and is restricted to intragenic regions of actively transcribing genes by EHMT2. Taken together, these observations reveal that H3S10ph may play a general role in restricting the spreading of repressive chromatin in interphase mammalian cells.